Presenting an Innovative Approach Combining FA and ANP Methods to Identify and Prioritize Water Pollutants in Petroleum and Petrochemical Industries - rohani, Abolfazl; Keramti, Abbas; Razmi, Jafar (Archives of Business Research, 2016)
Water contamination is one of the important challenges and problems of the world and Iran. One of the main causes of disease and mortality in the world is water contamination. Surface and ground waters are both subject to different contaminants. Considering the nature, origin of entrance of the pollutants, being natural or man-made, various classifications have been considered for contaminants. The major organic contaminants of water include agricultural, chemical, oil, and food contaminants. Each of these four groups has subcriteria. In this research, accurate investigation, identification, and ranking of water contaminants it all oil and petrochemical industries (urban area of Tehran province) have been dealt with using factor analysis and analytical network process methods. The results of factor analysis method suggest that the contaminants of nitrate, sodium, and TDH claimed the highest score by experts of environment in the field of water contamination. Furthermore, the results of analytical network process showed that agricultural contaminants with the weight of 0.321 stood in the first rank, while oil contaminants with the weight of 0.152 ranked the fourth.